Epistimology of Urf in the Usulul Fiqh - Mochamad Su’eb (EDUTEC : Journal of Education And Technology, 2018)
Science Fiqh is one of the sciences that need to be known by all Muslims because it involves Islamic laws. Overall, this knowledge is not easy to understand. Therefore, they need an introduction to this knowledge that is very important because it can direct understanding towards Fiqh true. In addition, as a scientific discipline, Fiqh will continue and must develop. Even so, the changes in history show dynamics. Sometimes it changes very rapidly. Sometimes it also looks slow. In fact, it is not uncommon to seem static. In fact, the demand for its development is a logical consequence of the burden and demands of changing society and Muslims themselves. In this paper, we will discuss something related to the social life of society, that is habit or in the language of Fiqh "Urf".